2014
DOI: 10.3855/jidc.4721
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae infection in hospitalized adult patients with community-acquired pneumonia in China

Abstract: Introduction: This study aimed to investigate the prevalence, clinical and radiographic features, and antibiotic responses of Mycoplasma pneumoniae (M. pneumoniae) infections in hospitalized adults with community-acquired pneumonia (CAP) in China. Methodology: Serum specimens collected from 189 CAP patients in both acute phase and convalescence were tested for IgG, IgA, and IgM mixed antibodies specific to M. pneumoniae. The clinical and radiographic characteristics and efficacy of three antibiotic regimens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…Although several multi-center studies regarding nation-wide epidemiology and etiology of CAP have been published recently, [5][6][7][8] the contemporary situation in reality remains attractive. The main reason results fromhuge publication biasbecause most Chinese clinical researchers have limited English writing skills, which means we probably failed to notice valuable data sealed within Chinese databases.…”
Section: Discussionmentioning
confidence: 99%
“…Although several multi-center studies regarding nation-wide epidemiology and etiology of CAP have been published recently, [5][6][7][8] the contemporary situation in reality remains attractive. The main reason results fromhuge publication biasbecause most Chinese clinical researchers have limited English writing skills, which means we probably failed to notice valuable data sealed within Chinese databases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PCR method was used to directly detect M. pneumoniae DNA, which has high specificity and sensitivity in clinical detection of M. Pneumoniae ( 11 , 12 ). But in clinical practice, co-infections are common in children with pneumonia and direct detection of M. pneumoniae is not efficient in distinguishing it from pneumonia ( 8 ). Our previous study suggested that Th 1 /Th 2 balance plays a significant part in anti-infectious immunity and Th 1 /Th 2 cytokines are useful biomarkers in diagnosis and treatment of bacterial and viral infection ( 13 - 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mycoplasma pneumoniae (MP) is one of the main pathogens of community-acquired pneumonia in children, and the incidence of mycoplasma pneumoniae pneumoniae (MPP) increased gradually [1] .…”
Section: Introductionmentioning
confidence: 99%